2020
DOI: 10.1149/1945-7111/abc5d8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Impurity Elements on Localized Corrosion of Zirconium in Chloride Containing Environment

Abstract: To clarify the mechanism of localized corrosion on zirconium in chloride environments, corrosion tests of zirconium and its alloys were performed using conventional and micron-scale measurement systems with surface areas of 0.35 cm2 and less than 0.04 cm2, respectively. The pitting potential significantly dropped by more than 1 V when zirconium was alloyed with over 10 mol% of tin. Zr4Sn and Zr5Sn3 intermetallics hindered the formation of passive films on the substrate. Additionally, tin was found on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…These results indicate that the corrosion-inducing properties of the inclusions are different. 26 The E pit value of Zr-0.5O-0.5C was approximately 0.8 V, and this was consistent with the repeated measurements. This corrosion behavior of Zr-0.5O-0.5C was unique compared to that of pure Zr and other Zr alloys.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…These results indicate that the corrosion-inducing properties of the inclusions are different. 26 The E pit value of Zr-0.5O-0.5C was approximately 0.8 V, and this was consistent with the repeated measurements. This corrosion behavior of Zr-0.5O-0.5C was unique compared to that of pure Zr and other Zr alloys.…”
Section: Methodssupporting
confidence: 83%
“…By using the micron-scaled electrochemical technique, inclusions such as Fe and Sn were found to trigger pitting corrosion. 26 However, there was a large difference in the degree of corrosion inductivity of each inclusion, resulting in a wide scattering of the pitting potential in the polarization curves. The reason for the large variation in the pitting potential of Zr is that the critical inclusions that trigger pitting z E-mail: manaka.met@tmd.ac.jp; TSUTSUMI.Yusuke@nims.go.jp corrosion at the lowest range of the applied potential seem to be rarely exposed to the surface of Zr.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that zirconium and its alloys are sensitive to pitting corrosion in environments containing chloride ions [29], which is expressed in destruction of the tin passive film and subsequent localization of the corrosion process. There is insufficient evidence in the scientific literature on the mechanism of corrosion of Zr-amorphous alloys and the reasons for propensity of Zr-amorphous alloys to pitting corrosion have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The authors' group investigated the relationship between the inclusions and the pitting corrosion of Zr using micron-scale electrochemical measurements. The numerous non-critical Fe-rich inclusions on the pure Zr surface trigger pitting corrosion under high applied potentials of more than 2 V. 28,32) The pitting potentials of more than 2 V under condition E indicated the elimination of all the critical inclusions via the A d v a n c e V i e w electrochemical treatment. However, the electrochemically treated Zr specimens under condition F occasionally underwent pitting corrosion at relatively low potentials of 1.4 and 1.8 V. The treatment efficiency per cycle under condition F was lowered possibly because the dissolution and release of the inclusions remained incomplete owing to the short anodic polarization time.…”
Section: Optimization Of the Electrochemical Treatment Conditionmentioning
confidence: 99%